Genetic Variants in COX2 and ALOX Genes and Breast Cancer Risk in White and Black Women - Mongiovi, Jennifer M.; Hong, Chi-Chen; Zirpoli, Gary R.; Khoury, Thaer; Omilian, Angela R.; Qin, Bo; Bandera, Elisa V.; Yao, Song; Ambrosone, Christine B.; Gong, Zhihong (Frontiers in Oncology, 2021)
COX and ALOX genes are involved in inflammatory processes and that may be related to breast cancer risk differentially between white and Black women. We evaluated distributions of genetic variants involved in COX2 and ALOX-related pathways and examined their associations with breast cancer risk among 1,275 white and 1,299 Black cases and controls who participated in the Women’s Circle of Health Study. Odds ratios (ORs) and 95% confidence intervals (CIs) were estimated using multivariable-adjusted logistic regression models. Our results showed differential associations of certain genetic variants with breast cancer according to menopausal and ER status in either white or Black women. In white women, an increased risk of breast cancer was observed for COX2-rs689470 (OR: 2.02, P=0.01) in the dominant model, and was strongest among postmenopausal women (OR: 2.72, P=0.02) and for estrogen receptor positive (ER+) breast cancers (OR: 2.60, P=0.001). A reduced risk was observed for ALOX5-rs7099874 (OR: 0.75, P=0.01) in the dominant model, and was stronger among postmenopausal women (OR: 0.68, P=0.03) and for ER+ cancer (OR: 0.66, P=0.001). Four SNPs (rs3840880, rs1126667, rs434473, rs1042357) in the ALOX12 gene were found in high LD (r2>0.98) in white women and were similarly associated with reduced risk of breast cancer, with a stronger association among postmenopausal women and for ER- cancer. Among Black women, increased risk was observed for ALOX5-rs1369214 (OR: 1.44, P=0.003) in the recessive model and was stronger among premenopausal women (OR: 1.57, P=0.03) and for ER+ cancer (OR: 1.53, P=0.003). Our study suggests that genetic variants of COX2 and ALOX genes are associated with breast cancer, and that these associations and genotype distributions differ in subgroups defined by menopausal and ER status between white and Black women. Findings may provide insights into the etiology of breast cancer and areas for further research into reasons for breast cancer differences between races.